Het geheim van de anatoom: Adolphe Burggraeve en de ontwikkeling van de Belgische anatomie in de negentiende eeuw - Deblon, Veronique; Huistra, Pieter (Studium, 2017)
The anatomist’s secret: Adolphe Burggraeve and the development of Belgian anatomy in the nineteenth century Lifelike and elegant preparations are often connected to an early modern anatomical tradition that had disappeared by the beginning of the nineteenth century. Anatomy’s transformation at the end of the eighteenth century caused anatomists to tone down the elaborate decorations of anatomical preparations. However, some anatomists still prepared lifelike preparations in the nineteenth century. Adolphe Burggraeve enriched the cabinet of the university of Ghent with multiple lifelike preparations for which he received scientific credit. Contrary to contemporary scientific standards his injection technique remained a secret. Burggraeve linked his preparations to the work of Frederik Ruysch by cultivating the secrecy surrounding his injection method which added prestige to Burggraeve’s status. Moreover, he was able to connect lifelike preparations to contemporary scientific debates. We argue that estheticized anatomical preparations were still a relevant anatomical practice in Belgian anatomy in the first half of the nineteenth century as their display for a medical and non-medical audience allowed anatomists to gain scientific prestige while also developing a national scientific discipline.